THE DIFFERENCES OF PROBLEM-FOCUSED COPING IN STUDENTS MAJORING IN HUMANITIES AND NON-HUMANITIES MAJORS - Utami, Stefanni Cahyani Indah; Widodo, Heri (SOLUTION, 2024)
This research aims to: (1) Find out whether there are differences in problem-focused coping in students majoring in humanities and non-humanities. (2) Find out how high problem- focused coping is for students majoring in humanities. (3) Knowing how high problem-focused coping is for students majoring in non-humanities. (4) Knowing which problem-focused coping scale items are identified and which items on the problem-focused coping scale are identified as low. This study is a comparative quantitative study that involves 200 respondents who are active students of the 2020-2022 batch of Sanata Dharma University Yogyakarta. There are two types of questionnaires in collecting the data in this study, there are an open questionnaire to determine the study program and class, and a closed questionnaire with a Likert Scale to calculate the problem-focused coping items of the students between the two sample groups. The questionnaire consists of 33 valid items, categorized into five aspects: self-activity, planning, minimizing competitive activities, self-control, and social support. The questionnaire's Alpha Cronbach reliability index was 0.722. As the assumption results were not met, the researcher used the Mann Whitney non-parametric t-test with the assistance of JASP 0.16.0.0 for Windows. The results of this study are: (1) There is a significant difference in problem-focused coping between students majoring in humanities and students majoring in non-humanities; (2) The level of problem-focused coping of students majoring in humanities tends to be in the high category; (3) The level of problem-focused coping of students majoring in non-humanities tends to be in the high category; (4) There are eight items with the number of item score achievements that are identified as moderate. So, the researchers propose guidance topics with the themes: (1) Deft in overcoming problems; (2) Planned life makes happy; (3) Building healthy relationships (4) Building positive openness.